What is the significance of the CCAFS Conference and Program? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Pramod Aggarwal of the Indian Agricultural Research Institute. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya